No place like home? . location choice and firm survival after forced relocation in the German machine tool industry - Guido Buenstorf; Christina Guenther (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
We study location choices and firm performance in the German machine tool industry, focusing on the forced migration of East German firms after World War II. Our analysis of location choices supports earlier findings that industry agglomerations attract further entrants. Relocating firms outperformed entrants that possessed no prior industry experience; apparently were able to build on their prewar capabilities. We find no evidence suggesting that firm performance benefited from agglomeration effects.
Keywords: L20; R12; R30; 330; Capabilities; agglomeration economies; location choice; firm survival; machine tool industry; Standortwahl; Lebenszyklus; Agglomerationseffekt; Werkzeugmaschinenbau; Deutschland (bis 1945); DDR; Deutschland